First Canadian Case Report of Kidney Transplantation From an HIV-Positive Donor to an HIV-Positive Recipient. Issue 1 (2nd March 2017) - Ambaraghassi, Georges; Cardinal, Héloïse; Corsilli, Daniel; Fortin, Claude; Fortin, Marie-Chantal; Martel-Laferrière, Valérie; Malaise, Jacques; Pâquet, Michel R.; Rouleau, Danielle
Rationale: Kidney transplantation has become standard of care for carefully selected patients living with human immunodeficiency virus (HIV) and end-stage renal disease (ESRD) in the highly active antiretroviral therapy (HAART) era. American and European prospective cohort studies have reported similar patient and graft survival compared with HIV-negative kidney transplant recipients. Despite an increased rate of acute rejection, partially due to drug interactions, HIV immunovirologic parameter generally remains under control during immunosuppression. A few cases of kidney transplantation between HIV-infected patients were done in South Africa and showed favorable results. No cases of kidney transplantation from an HIV-positive donor in Canada have previously been reported. Presenting concerns of the patient: A 60-year-old Canadian man with HIV infection presented in 2007 with symptoms compatible with acute renal failure secondary to IgA nephropathy. Chronic kidney disease resulted after the acute episode. Diagnoses: Hemodialysis was started in 2012. The patient was referred for a kidney transplantation evaluation. Interventions: The patient underwent kidney transplantation from an HIV-positive donor in January 2016. The recipient's antiretroviral regimen consisted of abacavir, lamivudine, and dolutegravir. No drug interactions have been reported between these antiretrovirals and the maintenance immunosuppressive regimen used. Outcomes: The outcome at 7 months post transplantation was excellent, with good graft function and adequate control of HIV replication, in the absence of opportunistic infections at a time when immunosuppression is at its highest intensity. No acute rejection was reported. An episode of bacteremic graft pyelonephritis due to Enterococcus faecalis was successfully treated after transplantation. Novel finding: With careful selection of patient, kidney transplantation between HIV-infected patients is a viable option. The use of antiretroviral drugs free of interactions simplified the dosing and management of the immunosuppressive drugs.